1997
DOI: 10.1128/jvi.71.4.2881-2886.1997
|View full text |Cite
|
Sign up to set email alerts
|

The NS3 proteinase domain of hepatitis C virus is a zinc-containing enzyme

Abstract: NS3 proteinase of hepatitis C virus (HCV), contained within the N-terminal domain of the NS3 protein, is a chymotrypsin-like serine proteinase responsible for processing of the nonstructural region of the HCV polyprotein. In this study, we examined the sensitivity of the NS3 proteinase to divalent metal ions, which is unusual behavior for this proteinase class. By using a cell-free coupled transcription-translation system, we found that HCV polyprotein processing can be activated by Zn 2؉ (and, to a lesser deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 38 publications
1
34
1
Order By: Relevance
“…As in HRV2-2A pro , the zinc site connects the interbarrel loop (ligands Cys97S γ and Cys99S γ ) with the turn between the β strands dII and eII (ligands Cys145S γ and a water molecule hydrogen bonded to His148). Nevertheless, the binding sites are not identical, as the zinc ion can be removed from the NS3 proteinase simply by dialysis against EDTA (Stempniak et al, 1997). In contrast, removal of the zinc ion from HRV2-2A pro requires prior denaturation of the enzyme with 8 M urea (Sommergruber et al, 1994b;Voss et al, 1995).…”
Section: The Hrv2-2a Pro Zinc Binding Sitementioning
confidence: 99%
“…As in HRV2-2A pro , the zinc site connects the interbarrel loop (ligands Cys97S γ and Cys99S γ ) with the turn between the β strands dII and eII (ligands Cys145S γ and a water molecule hydrogen bonded to His148). Nevertheless, the binding sites are not identical, as the zinc ion can be removed from the NS3 proteinase simply by dialysis against EDTA (Stempniak et al, 1997). In contrast, removal of the zinc ion from HRV2-2A pro requires prior denaturation of the enzyme with 8 M urea (Sommergruber et al, 1994b;Voss et al, 1995).…”
Section: The Hrv2-2a Pro Zinc Binding Sitementioning
confidence: 99%
“…Residues present in CTC motif (Cys481 and Cys483) and CHC motif (Cys457 and Cys 459) may be involved in zinc metal ion coordination and catalysis (Figure 9A). It is reported that the Zn binding site present on the opposite side of active site (Herold et al, 1999), which even validated by crystal structure of hepatitis C virus NS3 proteases (Stempniak et al, 1997;Barbato et al, 1999;Arasappan et al, 2005) picornavirus 2A (Yu and Lloyd, 1992) PL1pro of HCoV-229E (Ziebuhr et al, 2007), p150 of RUBV (Zhou et al, 2007), and Lpro of FMDV (Guarne et al, 2000). The diagrammatic representation indicates presence of CHC motif, opposite to the predicted active site, could be zinc binding site of HEV-protease (Figure 9).…”
Section: In Silico Analysis Of Hev-proteasementioning
confidence: 57%
“…The coordination of the structural zinc in the HCV NS3 proteinase is mediated by Cys-97, Cys-99, Cys-145, and His-149. A similar metal binding motif is found in 2A proteinases of enteroviruses and rhinoviruses, suggesting that they are structurally related [55].…”
Section: Picorna and Rhinovirusesmentioning
confidence: 67%
“…HCV polyprotein processing is activated by Zn 2+ and, to a lesser degree, by Cd 2+ , Pb 2+ , and Co 2+ and is inhibited by Cu 2+ and Hg 2+ ions [54]. Zn 2+ is not directly involved in catalysis but may have a structural role [55]. It is suggested that the three cysteines, and the histidines coordinate the structural zinc in the HCV NS3 proteinase at a Zn 2+binding site while dengue 2 virus NS3 protease, though lot of homology, does not contain a Zn 2+ -binding site [56].…”
Section: Hepatitis Virusesmentioning
confidence: 99%